2005
DOI: 10.1159/000087241
|View full text |Cite
|
Sign up to set email alerts
|

Degree of Cerebellar Ataxia Correlates with Three-Dimensional MRI-Based Cerebellar Volume in Pure Cerebellar Degeneration

Abstract: The aim of the present study was to compare the severity of cerebellar ataxia as measured by the International Cooperative Ataxia Rating Scale (ICARS) by Trouillas et al. [ J Neurol Sci 1997;145:205–211] with the cerebellar volume in chronic cerebellar disease. Fifteen patients with pure cerebellar degeneration were investigated. Seven patients suffered from spinocerebellar ataxia type 6, 5 from idiopathic late-onset cerebellar ataxia, 2 from autosomal dominant cerebellar ataxia type III and 1 from episodic at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 18 publications
2
24
3
Order By: Relevance
“…Richter et al 27 found significant correlations between lower limb ataxia and cerebellar volume in a heterogeneous group of patients with pure cerebellar degeneration, also including 7 patients with SCA6. In our present study, we were not able to replicate this finding in a homogeneous SCA6 cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Richter et al 27 found significant correlations between lower limb ataxia and cerebellar volume in a heterogeneous group of patients with pure cerebellar degeneration, also including 7 patients with SCA6. In our present study, we were not able to replicate this finding in a homogeneous SCA6 cohort.…”
Section: Discussionmentioning
confidence: 99%
“…We used conventional MRI-based volumetry to quantify the degree of atrophy of the cerebellum and its three longitudinal subdivisions in patients with cerebellar cortical degeneration. Total clinical ataxia rating scores showed a significant negative correlation with the volume of the entire cerebellum (normalised to the total intracranial volume) [12,13]. Oculomotor disorders were highly correlated with atrophy of the medial cerebellum.…”
Section: Somatotopy Motor Learningmentioning
confidence: 93%
“…Pons, V2, total brain stem, hemispheres and total cerebellum correlated with ICARS. ICARS seems to be a valuable clinical parameter since it has been demonstrated a relevant inverse correlation between this scale and cerebellar atrophy 24 . An inverse correlation was found between ICARS and spinal cord area in MJD/SCA3 patients although with no statistical significance 25 .…”
Section: Icarsmentioning
confidence: 99%